1786 Vt. Acts, Oct. Sess. 6 - (:unkn) unknown (My University, 1786)
Kept the minimum militia age at 16, but lowered the maximum age to 45. The gun mandate was changed to "a good musket or firelock." The bayonet was now mandatory. Made separate provisions for horsemen; each dragoon had to provide "a case of good pistols, a sword or cutlass not less than three and one half feet in length," plus a pound of gunpowder, "three pounds of sizeable bullets," and eight flints.656 Since horsemen would have at least two guns (the pair of handguns) they needed a bigger supply of flints.
Keywords: MILITIAS